Marketing Communication Strategy In Small Business Of Rokyati Crackers In Ulak Kerbau Baru Village (Ogan Ilir) - Ilham, Akbar; Isnawijayani, Isnawijayani (Sean Institute, 2024)
This research aims to analyze and disseminate marketing communication strategies implemented by the small business Kerupuk Rokyati in Ulak Kerbau Baru Village, Ogan Ilir. In an era of increasingly fierce competition, marketing communications plays an important role in strengthening the market and increasing product sales position. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews, observation and documentation. The results of the research show that the marketing communication strategy implemented by Kerupuk Rokyati is still conventional. Therefore, this research recommends the use of social media and digital platforms as a more modern marketing communications strategy to expand market reach and increase brand awareness.